(untitled) (Kinesiology, 2020)
Although maximal incremental exercise tests (GXT) are the gold standard for outcome assessment and exercise proscription, they are not widely available in either fitness or clinical exercise programs. This study compared the prediction of VO2max in healthy, sedentary volunteers using a non-exercise prediction (Matthews, Heil, Freedson & Pastides, 1999), RPE extrapolation to 19 & 20 (Eston, Lambrick, Sheppard & Parfitt, 2008) and the Rockport Walking Test (RWT)(Kline et al, 1987) and of VT using the Talk Test (Foster et al., 2018) and RPE @ 13,14,15. Subjects performed treadmill GXT with gas exchange, submaximal treadmill with RPE and Talk Test, the RWT and the Matthews non-exercise estimation. All methods provided reasonable estimates of both VO2max and VT, with correlations >0.75 and SEE 1 MET. VO2max was best estimated with extrapolation to RPE=19. VT was observed intermediate between the Last Positive & Equivocal stages of the TT and between RPE 13 & 14. Non-maximal evaluation, and even non-exercise equations can be used as a substitude for maximal GXT with gas exchange to make reasonable estimates of both VO2max and VT.